Tibiofemoral forces during FES rowing in individuals with spinal cord injury. Issue 3 (17th February 2021) - Chandran, Vishnu D.; Lambach, Rebecca L.; Gibbons, Robin S.; Andrews, Brian J.; Beaupre, Gary S.; Pal, Saikat
Abstract: The purpose of this study is to determine the tibiofemoral forces during functional electrical stimulation (FES) rowing in individuals with spinal cord injury (SCI). We analysed the motion of five participants with SCI during FES rowing, with simultaneous measurements of (i) three-dimensional marker trajectories, (ii) foot reaction forces (FRFs), (iii) ergometer handle forces, and (iv) timestamps for electrical stimulation of the quadriceps and hamstrings muscles. We created full-body musculoskeletal models in OpenSim to determine subject-specific tibiofemoral forces during FES rowing. The peak magnitudes of tibiofemoral forces averaged over five participants with SCI were 2.43 ± 0.39 BW and 2.25 ± 0.71 BW for the left and right legs, respectively. The peak magnitudes of FRFs were 0.19 ± 0.04 BW in each leg. The peak magnitude of handle forces was 0.47 ± 0.19 BW. Peak tibiofemoral force was associated with peak FRF (magnitudes, R 2 = 0.56, p = 0.013) and peak handle force (magnitudes, R 2 = 0.54, p = 0.016). The ratios of peak magnitude of tibiofemoral force to peak magnitude of FRF were 12.9 ± 1.9 (left) and 11.6 ± 2.4 (right), and to peak magnitude of handle force were 5.7 ± 2.3 (left) and 4.9 ± 0.9 (right). This work lays the foundation for developing a direct exercise intensity metric for bone mechanical stimulus at the knee during rehabilitation exercises. Clinical Significance: Knowledge of tibiofemoral forces from exercises such as FES rowing may provide clinicians the ability to personalize rehabilitation protocols to ensure that an SCI patient is receiving the minimum dose of mechanical stimulus necessary to maintain bone health.